pH/Reduction Dual Stimuli-Triggered Self-Assembly of NIR Theranostic Probes for Enhanced Dual-Modal Imaging and Photothermal Therapy of Tumors - Wang, Anna; Mao, Qiulian; Zhao, Meng; Ye, Shuyue; Fang, Jing; Cui, Chaoxiang; Zhao, Yan; Zhang, Yuqi; Zhang, Yu; Zhou, Feng; Shi, Haibin (Analytical chemistry (Washington), 2020)
Tumor microenvironment plays a pivotal role in the growth and metastasis of tumors, and has become a promising target for precise diagnosis and treatment of tumors. Herein, a novel smart NIR theranostic probe Cy-1 that can simultaneously respond to low intracellular pH and reductive glutathione (GSH) is reported. This probe has demonstrated to be able to intermolecularly undergo a biologically compatible CBT-Cys condensation reaction to selectively form large nanoaggregates in the tumor microenvironment resulting in its enhanced accumulation and retention in the tumor, which as a consequence significantly improves the sensitivity of NIR/photoacoustic imaging and photothermal therapeutic efficacy of tumors in living mice. We thus believe that this dual stimuli-mediated self-assembly strategy may offer a promising and universal platform for cancer theranostics.